2007
DOI: 10.1123/jab.23.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Plantar Pressure during Step Exercise in Different Floor Conditions

Abstract: Mechanical load has been estimated during step exercise based on ground reaction force (GRF) obtained by force platforms. It is not yet accurately known whether these measures reflect foot contact forces once the latter depend on footwear and are potentially modified by the compliant properties of the step bench. The aim of the study was to compare maximal and mean plantar pressure (PP), and maximal GRF obtained by pressure insoles after performing seven movements both over two metal force platforms and over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…GRFs have been measured in numerous studies involving walking, 17 dance leaps, 18 aerobic dance, [19][20][21] running, [22][23][24] hop for distance, 25 drop landings, [26][27][28][29] vertical dance jumps, 30 gymnastics, 31 and various other sports activities. [32][33][34][35] Vertical GRFs measured for the four tap dance sequences were in the lower range of those previously reported for the various activities (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…GRFs have been measured in numerous studies involving walking, 17 dance leaps, 18 aerobic dance, [19][20][21] running, [22][23][24] hop for distance, 25 drop landings, [26][27][28][29] vertical dance jumps, 30 gymnastics, 31 and various other sports activities. [32][33][34][35] Vertical GRFs measured for the four tap dance sequences were in the lower range of those previously reported for the various activities (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol was tested by Santos- Rocha and Veloso (2007). The subjects were allowed to familiarize with each speed by performing a few steps before data collection.…”
Section: Methodsmentioning
confidence: 99%
“…Step performance did not change when stepping on a force plate compared to a bench. The protocol was tested by Santos-Rocha and Veloso (2007). The subjects were allowed to familiarize with each speed by performing a few steps before data collection.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study has shown that the GRF obtained by force platforms are representative of those obtained in conditions of practice of Step-Exercise [13]. Spherical reflective markers were placed with double sided adhesive tape on the skin and on the shoe, on the right side of the body.…”
Section: Equipments and Materialsmentioning
confidence: 99%